2017
DOI: 10.1016/j.applanim.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus macaques ( Macaca mulatta ) displaying self-injurious behavior show more sleep disruption than controls

Abstract: Self-injurious behavior (SIB) is a pathology observed in both humans and animals. In humans, SIB has been linked to various mental health conditions that are also associated with significant sleep disruption. In rhesus macaques, SIB consists of self-directed biting which can range from mild skin abrasions to wounds requiring veterinary care. However, only one study suggests possible sleep disruption in macaques with SIB. We evaluated sleep disruption using a noninvasive system (infra-red camera and a video sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The relatively low activity during the middle 10 h of the lights-off period indicates that monkeys were, for the most part, asleep during this time. Previous studies have used video surveillance or actimeters to monitor nighttime activity in rhesus monkeys as a measure of sleep disturbance, with greater nighttime activity or awakenings indicating greater sleep disruption ( Golub and Hogrefe, 2016 ; Stanwicks et al, 2017 ). Thus, reduced nighttime activity during the middle 10 h of the lights-off period after 4 months suggests that sleep improved with age.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low activity during the middle 10 h of the lights-off period indicates that monkeys were, for the most part, asleep during this time. Previous studies have used video surveillance or actimeters to monitor nighttime activity in rhesus monkeys as a measure of sleep disturbance, with greater nighttime activity or awakenings indicating greater sleep disruption ( Golub and Hogrefe, 2016 ; Stanwicks et al, 2017 ). Thus, reduced nighttime activity during the middle 10 h of the lights-off period after 4 months suggests that sleep improved with age.…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals that present with self-inflicted injuries may never be observed exhibiting SIB, thus making it difficult to identify environmental triggers, if there are any. In such cases, the use of remote observations may be informative (Stanwicks et al, 2017).…”
Section: Sib With and Without Woundingmentioning
confidence: 99%
“…Although the mechanism underlying such dysregulation is not yet clear, one intriguing possibility involves epigenetic modifications of glucocorticoid receptor gene expression ( Matthews and McGowan, 2019 ). These factors interact to sensitize the animals to additional stress exposure and subsequently lead to disturbances in other neurobiological systems that manifest as increased aggressiveness ( Lutz et al, 2003a ), and sleep disruption ( Stanwicks et al, 2017 ). The development of SIB is then viewed as a coping response to ongoing stress exposure.…”
Section: The Model Of Self-injury In Rhesus Monkeysmentioning
confidence: 99%
“…These findings were later replicated in a different population of monkeys with and without SIB using infrared surveillance software that could reveal the timing of this activity as it occurred across the night. Using this approach, we found that monkeys with SIB compared to controls showed delayed sleep onset, higher overall activity at night, and longer bouts of activity when awake ( Stanwicks et al, 2017 ). Although these activity data are not definitive with respect to sleep since there was no monitoring of cerebral EEG, the results strongly suggest that several aspects of the sleep cycle (e.g., greater latency to sleep onset and less overall sleep) are abnormal in monkeys with SIB.…”
Section: The Model Of Self-injury In Rhesus Monkeysmentioning
confidence: 99%